2021
DOI: 10.1007/s42452-021-04587-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil salinity mapping using Landsat 8 OLI data and regression modeling in the Great Hungarian Plain

Abstract: Salt's deposition in the subsoil is known as salinization. It is caused by natural processes such as mineral weathering or human-made activities such as irrigation with saline water. This environmental issue has grown more critical and is frequently occurring in the Hungarian Great Plain, adversely influencing agricultural productivity. This study aims to predict soil salinity in the Great Hungarian Plain, located in the east of Hungary, using Landsat 8 OLI data combined with four state-of-the-art regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…For example, Nie et al ( 2021 ) evaluated the effectiveness of terrain factors such as DEM, slope, and TWI using kriging regression techniques in order to predict the extent of secondary salinization, in a setting of northeast China. Later, Sahbeni ( 2021 ) used field data and spectral salinity and vegetation indices derived from Landsat 8 OLI for developing soil salinity prediction maps in the Great Hungarian Plain using regression modeling. This study demonstrated the efficiency of the elevation factor which was statistically significant for soil salinity prediction, with a p value equal to 0.002, as in the case of this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nie et al ( 2021 ) evaluated the effectiveness of terrain factors such as DEM, slope, and TWI using kriging regression techniques in order to predict the extent of secondary salinization, in a setting of northeast China. Later, Sahbeni ( 2021 ) used field data and spectral salinity and vegetation indices derived from Landsat 8 OLI for developing soil salinity prediction maps in the Great Hungarian Plain using regression modeling. This study demonstrated the efficiency of the elevation factor which was statistically significant for soil salinity prediction, with a p value equal to 0.002, as in the case of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Since not all the CAM species are salt tolerant [ 35 ], the ice plant, as a halophyte, is a useful model for studying plant stress tolerance and enhanced water use efficiency. Considering that soil salinization has become worse and worse due to mineral weathering and irrational use of irrigation and fertilizers [ 36 ], the goal of this study was to uncover the molecular mechanisms underlying plant salt stress response and tolerance in the ice plant. The acquired knowledge may inform engineering and breeding efforts for stress-tolerant crops.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the potential of using remote sensing images such as Landsat coupled with ANNs to develop a model that can predict soil salinity might be a solution in data-poor areas (e.g. Libya) (Sahbeni, 2021).…”
Section: Soil Electrical Conductivity (Ec)mentioning
confidence: 99%